Standard Time Analysis on The Cutting and Packaging Section of Porridge Sticky Rice “JELITA” - Linggar Larasati; Iffan Maflahah; Burhan (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
The research aims to determine the standard working time on the cutting and packaging of glutinous jenang "JELITA". The cutting and packaging part is the part of the production process that determines the amount of production produced. The determination of standard time is done through the analysis of working methods and working time in those parts. The method used is the calculation of the standard time in the determination of operating process chart, left right handed chart, and flow diagrams. The results showed that improvements in working methods based on work maps were obtained based on proposed improvements. The proposed improvement results in the effectiveness and efficiency of the operating process time up to the layout on the work system, while in the determination of the default time produces 52 seconds of the standard time of the cutting process and 226 seconds of the raw time of the packaging process.